Communication and coordination of nursing in a high complexity health institution in Cartagena - Rosibel Prieto Silva (Universidad Nacional de Colombia, 2016)
Objective: To evaluate communication and coordination of nursing in a highly complex institution (ips) in Cartagena, Colombia. Methodology: A cross-sectional descriptive study was made. The population involved one hundred nurses who participated voluntarily. Information was collected by applying the Shortell´s et al. scales from Physician collaborative practice icu nurse questionnaire, validated for Colombian context with a Cronbach's Alpha of 0.92 for Communication -according to the definition of Irvine et al. (1)- and 0.82 for Coordination -according to the definition of Shortell et al (2). Results: The average scores of Communication dimension individually for all nurses of the same unit was 3.8 in the Emergency, Surgery, and Hospitalization Units; and 3.7, in the Intensive Care Unit and Special Programs. In respect of Coordination dimension, the average was of 3.9 in the surgery and hospital units; of 3.3 in Intensive Care Unit; and 3.8 in Emergency Room. Conclusion: Most of factors that make both Communication and Coordination dimensions among nurses and the health team were evaluated positively, with similar results in the units and average scores of individual-level scores for all nurses of the same unit. This facilitates that nursing optimally assume continuity of care regarding the interdependent role.